Dual high-strength steel eccentrically braced frames with removable links. - Dubina, D. (Earthquake engineering & structural dynamics.)
Structural damage in buildings designed according to the dissipative design philosophy can be significant, even under moderate earthquakes. Repair of damaged members is an expensive operation and may affect building use, which in turn increases the overall economic loss. If damage can be isolated to certain dissipative members realized to be removable following an earthquake, the repair costs and time of interruption of building use can be reduced. Dual structural configurations, composed of a rigid subsystem with removable ductile elements and a flexible subsystem, are shown to be appropriate for the application of removable dissipative element concept. Eccentrically braced frames with removable links connected to the beams using flush end-plate bolted connections are investigated as a practical way of implementing this design concept. High-strength steel is used for members outside links in order to enhance global seismic performance of the structure by constraining plastic deformations to removable links and reducing permanent drifts of the structure.